Soluble interleukin-2 receptor α and interleukin-2 serum levels in patients with basal cell carcinoma - Sobjanek, Michal; Bien, Ewa; Zablotna, Monika; Sokolowska-Wojdylo, Malgorzata; Sikorska, Monika; Lange, Magdalena; Nowicki, Roman (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction: Basal cell carcinoma (BCC) is an immunogenic neoplasm and the imbalance in Th1/Th2 cytokines expression seems to play the major role in pathogenesis and clinical behaviour of the tumour. Aim : To investigate the association of soluble interleukin 2α receptor (sIL-2Rα) and interleukin-2 (IL-2) serum concentrations with BCC. Material and methods : The study involved 110 individuals with BCC and 60 healthy age- and sex-matched volunteers. Serum levels of sIL-2Rα and IL-2 were measured using ELISA test. Results : We found significantly (p = 0.027) increased sIL-2Rα serum levels in BCC patients, in comparison to healthy controls. Statistically (p = 0.04) higher sIL-2Rα levels were observed in patients with more advanced tumours. Serum levels of sIL-2Rα showed a significant linear (r = 0.24, p = 0.018) correlation with tumour size. The average IL-2 serum levels in BCC patients were statistically (p = 0.039) decreased compared to controls. Significantly (p = 0.0454) lower median IL-2 levels were observed in patients with more advanced tumours. A negative correlation between sIL-2Rα and IL-2 serum concentrations was revealed (r = –0.22; p = 0.027). Conclusions : Our results testify to the importance of the IL-2/sIL-2Rα signalling pathway in pathogenesis of BCC, suggesting that IL-2 and sIL-2Rα might be considered as potential markers of disease and targets for immunotherapy in BCC patients.